Caracterização antropométrica e desfechos obstétricos de gestantes adolescentes brasileiras: uma revisão sistemática - Rocha, Maria Assunção Custódio (Brasil, 2022)
Introduction: During the gestational period the nutritional needs are increased the adequate feeding is paramount for the health of the mother and fetus. Objective: to describe about nutritional status and/or gestational weight gain of adolescent pregnant women considering the publications of the last five years. Material and methods: This is a systematic review in search of the databases: Medline, Lilacs and Scielo, in the period from 2016 to 2021. The descriptors used in combination were: in English "Adolescence; Pregnancy in Adolescence; Nutritional Status". Results and Discussion: Four articles were identified that fit the proposed objective. The analyzed articles identify that teenage pregnancy is a nutritional risk factor leading to some gestational intercourse (anemia, hypertensive syndrome, night blindness, etc). It also identified an increasing nutritional status of overweight and obesity in adolescent pregnant women. There is an association of gestational overweight with birth of GIG newborns and insufficient gestational weight gain with the birth of PIG newborns. The instruments used to assess nutritional status/weight gain in the articles were Institute of Medicine (IOM), Atalah et al. and WHO, methods most used in Brazil for nutritional assessment of pregnant women. Conclusion: This review found a small number of studies on nutritional assessment in adolescent pregnant women in the last five years. There is a need to pay special attention to this group in publications in the scientific environment with more recent information.